Analysis of Fatigue Performance of Metallic Components with Gradient Microstructures - Pandi Zhao; Liheng Tuo; Hongrui Zhang; Zhiyan Sun; Shuai Ren; Gaihuan Yuan; Zebang Zheng (Crystals)
Studying the fatigue performance of metallic components and optimizing their design from the perspectives of structure, microstructure, and service conditions has long been a critical research focus. In this study, a comprehensive analysis was conducted on the sealing performance and fatigue behavior of W-shaped metallic sealing rings with varying microstructures. A novel simulation approach is proposed that replaces explicit gradient definitions with temperature conduction to address the issue of stress concentration at interfaces in the finite element modeling of gradient structures. Based on this method, a macroscopic finite element model was developed to simulate the plastic strain accumulation and springback of the sealing ring in service. Then, taking the stress evolution at the trough position of the sealing ring during service as a boundary condition, the evolution of stored-energy density and fatigue life of rings with different microstructures, including both homogeneous and gradient configurations, was quantitatively evaluated. The findings of this work provide valuable insights for the design of structural parameters and the optimization of forming process parameters in high-performance sealing-ring applications.